THE INFLUENCE OF FINANCIAL LITERACY AND CUSTOMER TRUST ON INTEREST IN SAVING AT BANK NAGARI BRANCH KOTO BARUDHARMASRAYA REGENCY - Suandi, Edi; Anita, Uci (ADPEBI, 2024)
This study aims to determine the influence of financial literacy and customer trust on the interest in saving by respondents domiciled in Dharmasraya district. The sampling technique uses a simple random sampling technique, using the slovin formula so that a sample of 100 people is obtained. Research data collection technique through questionnaire with Likert scale. Based on the results of the calculation of the SPSS program application from the t-test, the financial literacy variable was obtained with a tcount of -2.219 and a value (sig= 0.029< 0.05) with df=100-3 = 97, then a table of 1.660 was obtained. From the above results, it can be seen that tcal< ttable or - 2,219<1,660 means that Ha is accepted and H0 is rejected. Therefore, it can be concluded that financial literacy has a positive and significant effect on the interest in saving by respondents domiciled in Dharmasraya district with a sig value = 0.029< 0.05. The customer trust variable with a calculation of 4,400 and a value (sig=0.000< 0.05) with df =100-3 = 97, then a table t of 1,660 was obtained. From the results above, it can be seen that tcal> ttable or 4,400 > 1,660 means that Ha is accepted and H0 is rejected. Therefore, it can be concluded that customer trust has a positive and significant effect on the interest in saving by respondents domiciled in Dharmasraya district. The F test was known that the value of Fcal> Ftable was 10.259>3.09 with a significance value of 0.000 or (0.000 < 0.05). So in this study, the independent variables together affect the dependent variables. The determination coefficient was obtained with a result of 0.175. This means that the variables of financial literacy and customer trust can explain the variable of saving interest by respondents domiciled in Dharmasraya district by 17.5%. The remaining 82.5% was explained by other variables that were not observed in this study.